Validation of an in vitro sun protection factor (SPF) method in blinded ring‐testing. (7th June 2018) - Pissavini, M.; Tricaud, C.; Wiener, G.; Lauer, A.; Contier, M.; Kolbe, L.; Trullás Cabanas, C.; Boyer, F.; Nollent, V.; Meredith, E.; Dietrich, E.; Matts, P. J.
Abstract: Objective: The objective of this work was to investigate the utility of a new in vitro SPF test method in blinded ring‐testing, against new ISO acceptance criteria. Methods: Twenty four blinded, commercial, emulsion‐type, primary sunscreen products, covering the full range of labelled SPF in Europe (SPF6 – 50+), were tested by three test institutes using the current ISO24444:2010 In Vivo SPF Test Method and simultaneously by three separate test laboratories using a new candidate in vitro SPF test method, developed under the leadership of Cosmetics Europe (CE). The resulting relationship between in vitro SPF and in vivo SPF values was then compared with acceptance criteria developed recently by the International Standards (ISO) TC217/WG7 Sun Protection Test Methods Working Group. Results: Analysis of the mean inter‐laboratory in vitro and mean inter‐institute in vivo SPF values revealed a strong correlation between in vitro and in vivo values, with a Pearson correlation coefficient of r 2 = 0.88 ( P < 0.0001), a slope of 1.01 and a non‐significant intercept (−1.48; P = 0.62). When these data were compared to the new ISO WG7 acceptance criteria, method bias was found to be extremely low and over 95% of the coupled data lay within the model 'funnel' (defined by upper and lower confidence intervals). Conclusion: In conclusion, the results of blinded ring testing and comparison to new ISO WG7 acceptance criteria indicate that a new in vitro SPF test method meets (and exceeds) these minimum criteria and is an interesting candidate for possible deployment as an industry test methodology. Abstract : ISO acceptance criteria 'funnel' and mean In Vivo In vitro data